1439 Principles of fitness for duty evaluations - Moyo, D. (BMJ Publishing Group, 2022)
Certifications for fitness for duty and return to work programs are an integral part of every medical practitioner’ duties. Fitness for duty decisions have a direct impact on employee availability and productivity in the workplace. Increasing trends of sickness absenteeism, presenteeism and declining organisational wellness indices have become a common trend as a result of subjective and unsound fitness for duty and return to work evaluations. The increasing use of dysfunctional and out-dated principles of light duty, indefinite sick leave and unqualified medical retirement among others that are desynchronized with occupational risk exposure profiles and person job specifications requires urgent redress.